Challenges in Solving Contextual Problems in Statistics Using the TEFA Approach Among Vocational Students - Nurbaiti, Idhata; Kusno, Kusno; Jazuli, Akhmad (Faculty of Teacher Training and Education, 2025)
This study explores the challenges faced by vocational students in solving contextual problems in statistics using the TEFA (Teaching Factory) approach, aimed at enhancing their analytical and problem-solving skills—competencies that are highly valued in the industrial world. The purpose of this research is to analyze the difficulties students encounter when solving TEFA-based contextual problems in statistical topics. The subjects of this study were 38 tenth-grade students from class X TO 9 at SMK Kesatrian Purwokerto, selected based on their even semester daily test scores. The students were categorized into three groups: high (HC), medium (MC), and low (LC), based on the class average and standard deviation. This research employed a qualitative descriptive method. The findings revealed that students in the high category were generally able to understand statistical concepts and accurately calculate the mean, median, and mode. However, some students in this group did not sort the data from smallest to largest when calculating the median. Students in the medium category had difficulty recalling how to compute the mean, often resulting in incorrect answers; although the mode was correct, the median was not. Meanwhile, students in the low category acknowledged that they lacked understanding of how to calculate the mean, median, and mode.